EXPLORING ANTICIPATED WARM GLOW IN SUSTAINABLE FOOD CONSUMPTION: A SYSTEMATIC LITERATURE REVIEW - Qurrotul Uyun; Olaf Ingmar; Tessa Azzahra; Fitriana Puji Astuti; Rismono; Umar Aminudin; Imam Syafii; Nasrowi Danu; Khairun Nisa; Agung Dharmawan Buchdadi (RADJA PUBLIKA, 2026)
The phenomenon related to Anticipated Warm Glow is becoming an important focus in individual purchasing decisions. People are motivated not only by economic factors but also by the actual moral basis of their actions, as well as by the positive emotions they anticipate feeling after doing good. Research on the concept of Anticipated Warm Glow in relation to the intention and decision to purchase sustainable food products has not been widely discussed. The misalignment between theory and empirical data in previous studies has led to an unstructured and unsystematic understanding. Therefore, this study aims to explore the influence of Anticipated Warm Glow on the intention and decision to purchase sustainable food products more systematically. The research method used is a systematic literature review with 27 articles analyzed on the concept of anticipated. The results indicate (1) the level of Anticipated Warm Glow is greatly influenced by the empathy possessed by consumers; (2) the emergence of Anticipated Warm Glow is influenced by internal and external factors; (3) the Anticipated Warm Glow that has emerged in consumers will affect their intention and purchasing decisions for sustainable food products; (4) the concept of Anticipated Warm Glow can be implemented in developing communication and promotion strategies for sustainable.